Rancangan Model Kewirausahaan antara Desa Balesari dan Desa Losari dalam rangka Mempertahankan Kearifan Lokal Daerah di Kabupaten Magelang - Endang Kartini Panggiarti (Monex: Journal of Accounting Research, 2020)
Balesari village on Windusari District and Losari Village on Grabag Distric are ones of region in Magelang District. The objective of the research is to find out about how entrepreneurship model design can be implemented for two villages and then can be comparable each other. This research are qualitative descriptive research. The descriptive research explained about the potential that belongs to Balesari and Losari village and develop entrepreneurship model with carry out local wisdom. The samples of the research about 10 – 15 respondent for each villages.The result of the research is that villages have unique characteristic. Entrepreneurship model design that can be arranged generally with this approach for know their society characteristic and method that their uses. Then describe to each entrepreneurship model for Balesari and Losari village. Balesari village because of near from city of Magelang have the society tend to be independent and less enthusiastic about receive the new something. This is opposite with Losari village. Losari village because it’s located far from the city of Magelang, the society of Losari village more open and very enthusiastic about the new something form team. For trying to introduce their self to the outside world, their open for the new something. This is difference principle about the difference society characteristic about Balesari and Losari village in Magelang district.